Pendayagunaan Wakaf Di Wakaf Mandiri Pada Masa Pandemi Covid-19 Perspektif Maqashid Al-Syariah - Khoirunnisa, Rofi’ah; Suryaningsih, Sri Abidah (Institute of Research and Community Service at Islamic University of Bunga Bangsa Cirebon, 2024)
Abstract The use of waqf instruments to solve social and economic problems provides an opportunity to deal with the Covid-19 pandemic. This article aims to analyze the use of waqf in Mandiri Waqf during the Covid-19 pandemic and its compatibility with the concept of maqashid sharia. The method used in this research is descriptive qualitative. The research was conducted by direct interviews with waqf institutions and supported by secondary data obtained from various sources. The results of the study show that in the perspective of maqashid sharia, the utilization of waqf in independent waqf is in line with the objective of waqf, namely that the principal assets of waqf must be maintained so that the benefits can be taken in the long term. The waqf program run by institutions during the pandemic can be divided into three according to the concept of the needs of Maqashid Syariah Imam As-Syatibi, namely dharuriyah, hajiyah, and tahsiniyah. Keywords: Waqf utilization; Maqashid sharia; Pandemicontent Abstrak Pemanfaatan instrumen wakaf untuk menyelesaikan permasalahan sosial dan ekonomi memberi peluang untuk menangani pandemi Covid-19. Artikel ini bertujuan menganalisis pemanfaatan wakaf di Wakaf Mandiri pada masa pandemi Covid-19 dan kesesuaiannya dengan konsep maqashid syariah. Metode yang digunakan dalam penelitian ini adalah kualitatif deskriptif. Penelitian dilakukan dengan wawancara langsung kepada pihak lembaga wakaf serta didukung data sekunder yang diperoleh dari berbagai sumber. Hasil penelitian menunjukkan bahwa dalam perspektif maqashid syariah, pendayagunaan wakaf di Wakaf Mandiri telah sesuai dengan tujuan wakaf yakni dimana harta pokok wakaf harus dijaga agar dapat diambil manfaatnya dalam jangka panjang. Program wakaf yang dijalankan oleh lembaga pada masa pandemi dapat dibagi menjadi tiga sesuai konsep kebutuhan pada Maqashid Syariah Imam As-Syatibi, yaitu dharuriyah, hajiyah, dan tahsiniyah. Kata Kunci: Pendayagunaan Wakaf; Maqashid Al-Syariah; Pandemi